Preliminary Trials on the Toxicity of "Algistat" to Fish and Algae - PAL, R. N.; GOPALAKRISHNAN, V. (Fishery Technology, 1968)
Preliminary toxicity trials conducted with "Algistat" (an algicide) indicated that a dose of 0 66 ppm. of the compound was highly toxic to fish and 0.8 ppm. was the general lethal level for Spirogyra sp. The blue green algae, Oscillatoria sp., Mycrocystis sp. and Anabaena sp. were adversely affected by dosages higher than 0.5 ppm. Euglena sp. was not affected even at 1.0 ppm.